Cost‐effectiveness of clinical interventions for delirium: A systematic literature review of economic evaluations. (31st May 2022) - Kinchin, Irina; Edwards, Layla; Hosie, Annmarie; Agar, Meera; Mitchell, Eileen; Trepel, Dominic
Abstract: Objective: Little is known about the economic value of clinical interventions for delirium. This review aims to synthesise and appraise available economic evidence, including resource use, costs, and cost‐effectiveness of interventions for reducing, preventing, and treating delirium. Methods: Systematic review of published and grey literature on full and partial economic evaluations. Study quality was assessed using the Consolidated Health Economic Evaluation Reporting Standards (CHEERS). Results: Fourteen economic evaluations (43% full, 57% partial) across nine multicomponent and nonpharmacological intervention types met inclusion criteria. The intervention costs ranged between US386 and 553 per person in inpatient settings. Multicomponent delirium prevention intervention and the Hospital Elder Life Program (HELP) reported statistically significant cost savings or cost offsets somewhere else in the health system. Cost savings related to inpatient, outpatient, and out‐of‐pocket costs ranged between 194 and 6022 per person. The average CHEERS score was 74% (±SD 10%). Conclusion: Evidence on a joint distribution of costs and outcomes of delirium interventions was limited, varied and of generally low quality. Directed expansion of health economics towards the evaluation of delirium care is necessary to ensure effective implementation that meets patients' needs and is cost‐effective in achieving similar or better outcomes for the same or lower cost.